Adoption and profitability of BARI lentil varieties in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2013)
Lentil is an important pulse crop widely grown in Bangladesh. It ranks first among the pulses in terms of area and consumers preference. BARI has developed many improved lentil varieties and disseminated to the farmers fields. The up-to-date information regarding adoption and financial profitability of this crop are unknown to the researchers and policymakers. Therefore, the study was conducted in Jhenaidah and Jessore districts to determine the adoption status and profitability of BARI lentil production and to examine the factors affecting the yield of BARI lentil during 2010-2011. Cobb-Douglas production function was used. The study revealed that 98% of the total lentil cultivated areas were occupied by BARI lentil varieties in the study areas. The average level of adoption of BARI Masur-3, BARI Masur-4, BARI Masur-5 and BARI Masur-6 were 49%, 47%, 1% and 1%, respectively at farm level. The cultivation of BARI lentil was profitable to the farmers since the per hectare total cost, gross return and net return of BARI lentil cultivation were Tk 52,734, Tk 80,572 and Tk 27,838, respectively. Functional analysis revealed that seed, urea, mechanical power cost and pesticides had positive effect on the yield of lentil production. Unavailability of latest BARI lentil seed, lack of technical know-how, lack of training, and diseases (root rot and stemphylium blight) were the main constraints to BARI lentil cultivation at farm level. BARI Masur-3 and BARI Masur-4 were the highly adopted varieties. The lentil production was profitable to the farmers in the study areas DOI: http://dx.doi.org/10.3329/bjar.v37i4.14384 Bangladesh J. Agril. Res. 37(4): 593-606, December 2012